Researching reciprocal leadership: Using the consciousness quotient inventory (CQ-i) as a pilot methodology to explore leadership with the context of a school–university partnership. (January 2018) - Poultney, Val; Fordham, Jon
This article looks at the potential of using an online self-completing inventory that measures leadership consciousness awareness. The Consciousness Quotient inventory (CQ-i) has been developed to encourage leaders to be more conscious of their ability to be accountable and responsible for their leadership practice. The CQ-i as a method for researching leadership is piloted here between a university academic and a primary headteacher in the context of a school–university partnership. Pilot outcomes reveal that the inventory can be used as an evaluation of partnership work and ways of thinking about leadership on two levels: the personal and the partnership. The method is somewhat limited by a lack of distinctive criteria for personal domain statements and the absence of an overall profile outcome for the CQ score. Its strength lies in the way the outcomes of the inventory can be used as a starting point for personal reflection on leadership and as a vehicle for discussing a range of different ways of leadership working within different settings, such as school and university contexts.